FOSTERING CLOSER RELATIONSHIP THROUGH ARTWORK EXHIBITION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, April 2016 – The '2 Series Artwork' from Thailand, "Space and Time of Serenity" by Manee Meemak and "Colour of Faith and Serenity” by Pongsiri Kiddee held at the Muzium & Galeri Tuanku Fauziah (MGTF), Universiti Sains Malaysia (USM) would help to foster closer relationship between USM and the Thailand universities concerned.